The media competence Andalusian seniors: challenges for full social inclusion - Contreras Pulido, Paloma; Marfil-Carmona, Rafael; María Ortega, Juana (Historia y Comunicación Social, 2014)
Older people in current society represent a high percent age that tends to be higher over the years. In addition, these seniors are becoming more active within this society taking part of even the developments resulting from the use of digital technologies. This paper analyzes the level of media literacy of people over 55 years in the Autonomous Community of Andalusia.
Keywords: Media competence; seniors; Andalusia; media literacy; social inclusion.